Global street design guide - Global Designing Cities Initiative (London; Island Press, 2016)
Each year 1.2 million people die from traffic fatalities, highlighting the need to design streets that offer safe and enticing travel choices for all people. Cities around the world are facing the same challenges as cities in the US, and many of these problems are rooted in outdated codes and standards. The Global Street Design Guide is a timely resource that sets a global baseline for designing streets and public spaces and redefines the role of streets in a rapidly urbanizing world. The Guide will broaden how to measure the success of urban streets to include: access, safety, mobility for all users, environmental quality, economic benefit, public health, and overall quality of life. The first-ever worldwide standards for designing city streets and prioritizing safety, pedestrians, transit, and sustainable mobility are presented in the Guide. Participating experts from global cities have helped to develop the principles that organize the Guide. The Guide builds off the successful tools and tactics defined in NACTO's Urban Street Design Guide and Urban Bikeway Design Guide while addressing a variety of street typologies and design elements found in various contexts around the world. This innovative guide will inspire leaders, inform practitioners, and empower communities in realizing the potential in their public space networks. It will help cities unlock the potential of streets as safe, accessible and economically sustainable places.
Note continued: 11.6.Neighborhood Gateway Intersection -- 11.7.Intersection of Two-Way and One-Way Streets -- 11.8.Major Intersection: Reclaiming the Corners -- 11.9.Major Intersection: Squaring the Circle -- 11.10.Major Intersection: Cycle Protection -- 11.11.Complex Intersection: Adding Public Plazas -- 11.12.Complex Intersection: Improving Traffic Circles -- 11.13.Complex Intersection: Increasing Permeability -- Resources -- Acknowledgments -- Key Terms -- Notes -- References -- Appendix -- A.Conversion Chart -- B.Metrics Charts -- Physical and Operational Changes -- Use and Functional Changes -- Evaluating the Impacts -- C.Summary Chart of Typologies Illustrated -- D.User Section Geometries -- E.Assumptions for Intersection Dimensions.
Recommended by Cyrus Qureshi
Includes bibliographical references (pages 372-376) and index.
Keywords: City traffic -- Planning; Streets -- Design and construction; Pedestrian facilities design; Streets -- Planning; Traffic calming; ARCHITECTURE / Urban & Land Use Planning; TRANSPORTATION / Public Transportation; City traffic -- Planning; Pedestrian facilities design; Streets -- Design and construction; Streets -- Planning; Traffic calming; Verkehrsplanung; Strassengestaltung